Modeling Multi-Agent Self-Organization through the Lens of Higher Order Attractor Dynamics - Butner, Jonathan E.; Wiltshire, Travis J.; Munion, A. K. (Frontiers in Psychology, 2017)
Social interaction occurs across many time scales and varying numbers of agents; from one-on-one to large-scale coordination in organizations, crowds, cities, and colonies. These contexts, are characterized be emergent self-organization that implies higher order coordinated patterns occurring over time that are not due to the actions of any particular agents, but rather due to the collective ordering that occurs from the interactions of the agents. Extant research to understand these social coordination dynamics has primarily examined dyadic contexts performing rhythmic tasks. To advance this area of study, we elaborate on attractor dynamics, our ability to depict them visually, and quantitatively model them. Primarily, we combine difference/differential equation modeling with mixture modeling as a way to infer the underlying topological features of the data, which can be described in terms of attractor dynamic patterns. The advantage of this approach is that we are able to quantify the self-organized dynamics that agents exhibit, link these dynamics back to activity from individual agents, and relate it to other variables central to understanding the coordinative functionality of a system’s behavior. We present four examples that differ in the number of variables used to depict the attractor dynamics (1,2,and 6) and range from simulated to non-simulated data sources. We demonstrate that this is a flexible method that advances scientific study of social coordination dynamics in a variety of multi-agent systems.